Optimization of Seed Potato (Solanum tuberosum L.) Production: Effects of Pre-Sowing Gibberellic Acid Treatments and Planting Density - Arif ŞANLI; Yeşim CİRİT (Yüzüncü Yil Üniversitesi Tarim Bilimleri Dergisi, 2020)
This research was carried out in 2016 and 2017 in Isparta conditions in order to determine the effectiveness of pre-sowing gibberellic acid applications and planting density on seed potato tuber production. In this study, GA3 was applied to seed tubers at 0, 1.5, 3.0 and 4.5 ppm before planting and tubers were planted at different in-row spacing (20, 25 and 30 cm). GA3 applications significantly increased the number of main stem, number of tubers per hill, seed tuber yield and total tuber yield. As the planting density increased, number of tubers per hill, tuber yield per hill and average tuber weight decreased while seed tuber yield and total tuber yield increased. Planting at 20 cm in-row spacing by applying 3.0 and 4.5 ppm GA3 were the most effective applications in terms of seed tuber yield and the Grade A seed tuber yield increased by 57% and Grade B seed tuber yield increased by 88% with these treatments. In the study, it was understood that seed grade tuber yield could be increased without decreasing in total tuber yield with planted of tubers at a distance of 20 cm in-row spacing by applying 3.0 ppm GA3 before planting.